The Eternal Problems Of God’s (In)activity in the World and How to Reconcile the “God of Philosophy” with the “God of Revelation”. Reflections Based on Miłosz Hołda’s Book Źródło i noc. Wprowadzenie do współczesnego absconditeizmu - Słomka, Marek (Roczniki Filozoficzne, 2023)
In the book Źródło i noc. Wprowadzenie do współczesnego absconditeizmu [The Spring and the Night: An Introduction into Contemporary Absconditheism] (Kraków: Wydwnictwo WAM, 2020), Miłosz Hołda thoroughly presents the discussed issues and proposes interesting solutions. When being an ambitious attempt to elaborate an original position in an vital area of Christian thought, the publication calls for critical reflection and highlighting main problems, which is the purpose of this text. It is especially about two questions of key importance for theism: God’s (in)activity in the world and how to reconcile the “God of philosophy” with the “God of revelation.” In the first one, the basic problem consists not only in the (partially) incorrect approach to the scientific picture of the world, but also to the philosophy of science and theology of science. In the second area, the main shortcoming of Hołda’s analyzes is the discrepancy between the manifested support for classical theism and the lack of a critical look at its elements that make it difficult, and in some aspects impossible, to express the essential content of the Judeo-Christian revelation. The remarks contained in the article do not completely refute the principal theses put forward by Hołda, but lead to their modification, and emphasize the value of a scientific worldview.